Effect of Facile p-Doping on Electrical and Optoelectronic Characteristics of Ambipolar WSe2 Field-Effect Transistors - Junseok Seo; Kyungjune Cho; Woocheol Lee; Jiwon Shin; Jae-Keun Kim; Jaeyoung Kim; Jinsu Pak; Takhee Lee (Nanoscale Research Letters, 2019)
Abstract We investigated the electrical and optoelectronic characteristics of ambipolar WSe2 field-effect transistors (FETs) via facile p-doping process during the thermal annealing in ambient. Through this annealing, the oxygen molecules were successfully doped into the WSe2 surface, which ensured higher p-type conductivity and the shift of the transfer curve to the positive gate voltage direction. Besides, considerably improved photoswitching response characteristics of ambipolar WSe2 FETs were achieved by the annealing in ambient. To explore the origin of the changes in electrical and optoelectronic properties, the analyses via X-ray photoelectron, Raman, and photoluminescence spectroscopies were performed. From these analyses, it turned out that WO3 layers formed by the annealing in ambient introduced p-doping to ambipolar WSe2 FETs, and disorders originated from the WO3/WSe2 interfaces acted as non-radiative recombination sites, leading to significantly improved photoswitching response time characteristics.